Italy - Gzik, Michał (The Role of Regions in EU-China Relations, 2021)
Fast growing network of national contacts in the Sino-Italian affairs builds the important layer of subnational bilateral relations. The main purpose of this paper is to analyze the role of paradiplomatical cooperation between Italian and Chinese regions. This paper contains a short overview of bilateral Italian-Chinese relations in political, economic and social terms. Furthermore there is a description of competences of the regions in the Italian foreign policy in term of legal environment for the autonomous activities of Italian regions in the international arena. Moreover this paper contains the analyses of existing links between Italian and Chinese regions on the basis of a survey conducted among regional authorities from all Italian regions. Finally it contains the case of Umbria, as a region that active cooperation with China goes well beyond economic relations.